Human Trafficking and Moral Panic in Cambodia. Issue 1 (May 2014) - Keo, Chenda; Bouhours, Thierry; Broadhurst, Roderic; Bouhours, Brigitte
This article examines the backgrounds of traffickers in Cambodia: why they became involved in trafficking, how they operate, their earnings, and the criminal justice system's response to their activities. Our research draws from interviews with justice officials, NGOs, and detained alleged traffickers; and from a review of police and prison records. The results challenge alarmist claims about the high prevalence, profitability, or role of organized crime in human trafficking. In Cambodia, 80 percent of incarcerated traffickers are poor uneducated women who lack legitimate opportunities and whose unsophisticated illicit activities earn very little. We argue that the Cambodian government, in return for foreign aid, adopted a repressive law that defines human trafficking ineptly; in the hands of a dysfunctional justice system, the law has turned into an instrument of corruption and injustice against powerless individuals.